‘To Fill Yourself with Goodness’: Revolutionary Self‐Making in Bolivarian Venezuela. - WILDE, M. A. T. T. (Bulletin of Latin American Research, 2018)
This article explores how utopian visions are articulated by chavista activists in Venezuela through the practice of “revolutionary self‐making”. Drawing on ethnographic fieldwork conducted in the city of Valencia between 2008 and 2012, it aims to demonstrate how close attention to the formation of new moral and spiritual selves is an integral part of the way that chavistas enact and experience political protagonism. In doing so, the article seeks to provide a ground level view of utopian visions as they are manifested discursively and practically in everyday life.